СТРАТЕГІЯ МЕТОДИКИ ВПРОВАДЖЕННЯ ІНФОРМАЦІЙНИХ ТЕХНОЛОГІЙ У ПРОЦЕС НАВЧАННЯ (Педагогіка вищої та середньої школи, 2010)
In this article ways of readiness of the future teachers to use of competition technologies in education process are considered.